2015
DOI: 10.7314/apjcp.2015.16.3.1235
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FHIT Gene Methylation in Egyptian Breast Cancer Women: Association with Clinicopathological Features

Abstract: Background: Fragile histidine triad (FHIT) gene is a tumor suppressor gene which involved in breast cancer pathogenesis. Epigenetics alterations in FHIT contributes to tumorigenesis of breast cancer. Objective: Our objective was to study FHIT promoter region hypermethylation in Egyptian breast cancer patients and its association with clinicopathological features. Materials and Methods: Methylation-specific polymerase chain reaction was performed to study the hypermethylation of FHIT promoter region in 20 benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The contribution of epigenetic factors to risk and prognosis of breast cancer reported in Africa included the roles of tissue microRNA, circulating free mRNA, circulating long non-coding RNA ( 158 163 ) as well as DNA methylation status of breast cancer susceptibility genes like APC , ERα , RASSFIA , UCHL1 , COX-2 , and FHIT ( 161 , 164 167 ) in breast tumor across Africa.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of epigenetic factors to risk and prognosis of breast cancer reported in Africa included the roles of tissue microRNA, circulating free mRNA, circulating long non-coding RNA ( 158 163 ) as well as DNA methylation status of breast cancer susceptibility genes like APC , ERα , RASSFIA , UCHL1 , COX-2 , and FHIT ( 161 , 164 167 ) in breast tumor across Africa.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis performed by Wu et al (13) indicated that FHIT hypermethylation, which induces the inactivation of the FHIT gene, is associated with an increased risk and adverse clinical outcome of NSCLC. It has been demonstrated that FHIT promoter hypermethylation is associated with the development of breast cancer and certain poor prognostic features of the disease (14). FHIT may be a potential drug target for the development of demethylation treatment for patients with breast cancer (44).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is a well-studied epigenetic modification, which significantly contributes to leukemia development (12). Several studies have demonstrated an association between FHIT hypermethylation and an increased risk of non-small-cell lung carcinoma (NSCLC) (13), breast cancer (14,15), cervical cancer (16), hepatocellular carcinoma (17) and thyroid carcinoma (18). Furthermore, downregulation of FHIT expression has been observed in acute lymphoblastic leukemia (ALL) (19), gastric cancer (20), colon adenocarcinoma (21), nasopharyngeal carcinoma (22) and colorectal cancer (23).…”
Section: Introductionmentioning
confidence: 99%
“…Its 5-year survival rate is only 10%, and the liver transplantation is considered as the only radical method for primary HCC. Patients with advanced HCC and unresectable liver constitute the vast majority (over 80%) (7,8). The latest developed interventional embolotherapy has become the main method for primary HCC.…”
Section: Discussionmentioning
confidence: 99%